2019
DOI: 10.1007/s00167-019-05732-8
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injection of culture-expanded mesenchymal stem cells with or without addition of platelet-rich plasma is effective in decreasing pain and symptoms in knee osteoarthritis: a controlled, double-blind clinical trial

Abstract: Purpose To compare the clinical and laboratory outcomes of intra-articular injections of culture-expanded bone-derived mesenchymal stem cells (MSCs) with or without platelet-rich plasma (PRP) to intra-articular corticosteroid injections for the treatment of knee osteoarthritis (OA). Methods Forty-seven patients with radiographic and symptomatic knee OA were randomized into three groups for intraarticular injections: autologous bone marrow-derived culture-expanded MSCs (n = 16); autologous bone marrow-derived c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
100
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 51 publications
0
100
0
3
Order By: Relevance
“…Reporting a clinical study with 18 patients, Bastos et al concluded that the use of PRP as co-adjuvant together with 40 million BM-MSCs did not provide additional bene ts over the use of BM-MSCs alone [37]. The same group, in a recent clinical trial, compared the use of 40 million BM-MSCs (n=14) with and without PRP (n=16) and corticosteroids (n=17) as standard control treatment, no differences were observed in the use of adjuvant therapy with PRP in the treatment of these patients [17]. Interestingly, Bastos et al reported the use of a white blood cell-depleted PRP (<0.3% from the initial red blood cells and leukocytes were present) containing between 5.4-to 7.3-fold increase in platelet concentration (1.4x10 6 to 1.9 x 10 6 platelets/μl).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Reporting a clinical study with 18 patients, Bastos et al concluded that the use of PRP as co-adjuvant together with 40 million BM-MSCs did not provide additional bene ts over the use of BM-MSCs alone [37]. The same group, in a recent clinical trial, compared the use of 40 million BM-MSCs (n=14) with and without PRP (n=16) and corticosteroids (n=17) as standard control treatment, no differences were observed in the use of adjuvant therapy with PRP in the treatment of these patients [17]. Interestingly, Bastos et al reported the use of a white blood cell-depleted PRP (<0.3% from the initial red blood cells and leukocytes were present) containing between 5.4-to 7.3-fold increase in platelet concentration (1.4x10 6 to 1.9 x 10 6 platelets/μl).…”
Section: Discussionmentioning
confidence: 98%
“…In that sense, Caplan et al proposed a change in the name of MSCs from mesenchymal stromal cells to medicinal signaling cells [4,43]. This change in nomenclature is explained because paracrine effects of MSCs on in ammatory cells, and recently a decreased level of in ammatory cytokines (IL-17a, IL-10 and TNF-a) with the administration of BM-MSC have been reported [17]. Futures studies should focus on the lower OA grades to delimit the paracrine effects of biological treatments in chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although treatment with MSCs in knee OA has been shown as a safe and feasible procedure in numerous phase I and II clinical trials, there are still doubts about its efficacy, mechanism of action, dosing and use of adjuvants [16][17][18][19]. Thus, the good preliminary results in safety have encouraged clinicians to conduct clinical trials focused on the efficacy of MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Irreversible injuries of the hierarchical osteochondral (OC) tissue, triggered by different pathological conditions, can affect both the articular cartilage and the subchondral bone. Currently, autografts or allografts, bone marrow stimulation, cell-based therapy with autologous chondrocytes implantation, and intra-articular injections of mesenchymal stem cells with platelet-rich plasma (PRP), are the most common surgical methods used for OC tissue treatment (Zhang et al, 2016;Devitt et al, 2017;Bastos et al, 2019). Nevertheless, these treatments are able to reduce pain and cannot warrant the complete regenerative process of the tissue and the articular cartilage healing (De L'Escalopier et al, 2015).…”
Section: Introductionmentioning
confidence: 99%